Stochastic differential equations on imbedded manifolds - Gikhman, I. I.; Klychkova, I. E.; Гихман, И. И.; Клычкова, И. Е.; Гихман, И. И.; Клычкова, И. Е. (Institute of Mathematics, NAS of Ukraine, 1995)
We construct a solution of a stochastic differential equation on an imbedded manifold in the case where the ambient manifold is a Euclidean space.